La comunicazione come strumento infermieristico per l'empowerment del paziente in dialisi - Patrizia Quaranta; Debora Giudice; Michele Fersurella; Giorgio Merola; Graziano Minonne; Vincenzo Montinaro (AboutScience Srl, 2019)
When a patient with chronic renal failure is told he must undergo hemodialysis, he/she lives an emotional shock, followed by a phase of anxiety. If this shock can't be overcome, the patient can face some anxious-depressive pathologies that will complicate the already complex clinical picture. The aim of this work is to demonstrate how the communicative/educational measures are the clinical instruments, applied especially by nurses, that lead the patient to the acquisition of different skills (such as self-reliance and psycho-social abilities). In conclusion, an efficient communication, mainly based on active and participative listening, represents the most effective instrument for the patient with chronic-degenerative pathologies to promote the awareness of his own capacities of self-management, and to make him play a leading role in his own health. (narrative nephrology)